Legal Problems of Inheritance Clauses for Cryptocurrency Digital Assets in Indonesia - Andi Mumtaz Jamaluddin Fatwa; Ahmad Fajruddin Fatwa; Muhammad Waliyuddin Yusuf; Muflikhatul Khoiroh; Suqiyah Musafa'ah (Penerbit Goodwood, 2026)
Purpose: The study examines the legal uncertainty surrounding cryptocurrency inheritance in Indonesia due to the absence of specific regulations and different interpretations among Islamic legal authorities.Research Methodology: This research uses a normative juridical method with a qualitative approach through a literature review. The study analyzes Qur’anic inheritance verses, contemporary Islamic jurisprudence, and Indonesian legal regulations related to digital assets. Secondary data were obtained from academic literature, journal articles, and institutional opinions issued by the Majelis Ulama Indonesia (MUI), Nahdlatul Ulama (NU), and Muhammadiyah.Results: MUI and Muhammadiyah generally prohibit cryptocurrencies for gharar and maisir reasons, while some NU forums allow them conditionally. The findings show that cryptocurrencies can qualify as inherited property only if they meet the principles of Islamic law and recognized ownership requirements.Conclusions: Cryptocurrencies cannot be automatically treated as inherited property under Islamic law because their legal status depends on compliance with sharia and the absence of a comprehensive legal framework for digital inheritance in Indonesia.Limitations: This study is limited to normative legal analysis and does not include empirical data regarding inheritance disputes involving cryptocurrency.Contributions: The study proposes a normative legal framework for cryptocurrency inheritance by integrating Islamic heritage principles, Indonesian digital asset regulation, and institutional fatwas, and provides a theoretical basis for future legal reforms.